Representation of feminism in Miss & Mrs. Cops (John Fiske’s semiotic analysis) - Lukman Hakim; Wina Kurnia (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
Oppression of women is still common today. Feminism is a social movement that strives to uphold justice for women. Feminists are doing various ways to voice and resuscitate society about gender discrimination against women. Film media is one of the tools used by feminists to make people aware of the issue. Film media was chosen because the film is considered capable of influencing and shaping society based on the messages it conveys.